DEGRADASI ZAT WARNA SUDAN I SECARA SONOLISIS DAN FOTOLISIS DENGAN PENAMBAHAN TiO2-ANATASE - -, Safni; Loekman, Umiati; Febrianti, Fitra; -, Maizatisna; Sakai, Tadao (Jurnal Riset Kimia, 2008)
ABSTRACT Degradation of Sudan I dye had been done with sonolysis and photolysis by adding anatase-TiO2.  Sonolysis method were performed using an ultrasound with frequency  of 45 kHz. Photolysis method were performed using an irradiation of UV light with λ = 359 nm.  Degradation of 4 mg/L Sudan I with addition of 0.1000 g anatase-TiO2 at pH = 7.0, temperature 25 ± 1°C, percentage of degradation 64.04% within 180 minutes sonolysis.  Degradation of 4 mg/L Sudan I using photolysis with addition of 0.1000 g anatase-TiO2 at pH = 7.0 and percentage of degradation 100% within 180 minutes photolysis. Degradation of 4 mg/L Sudan I using sonolysis and photolysis  simultaneously with addition of 0.1000 g anatase-TiO2 at pH = 7.0 and percentage of degradation 94.04% within 180 minutes treatment.   Keywords : degradation, sonolysis, photolysis, Sudan I, anatase-TiO2.